2020
DOI: 10.1186/s43066-019-0013-8
|View full text |Cite
|
Sign up to set email alerts
|

Main insights of genome wide association studies into HCV-related HCC

Abstract: Background: Hepatocellular carcinoma (HCC) is one of the most common causes of cancer-mortality globally. Hepatocarcinogenesis is a complex multifactorial process. Host genetic background appeared to play a crucial role in the progression of HCC among chronic hepatitis C patients, especially in the era of Genome Wide Association Studies (GWAS) which allowed us to study the association of millions of single nucleotide polymorphisms (SNPs) with different complex diseases. This article aimed to review the discove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…It may be that these polymorphisms weaken the activity of DEPDC5, preventing it from inhibiting mTORC1 as it does normally, which in turn leads to pathogenic inflammation and cell growth in the liver [ 22 , 29 ]. Future research should explore how the rs1012068 and rs5998152 polymorphisms affect DEPDC5 expression and activity.…”
Section: Discussionmentioning
confidence: 99%
“…It may be that these polymorphisms weaken the activity of DEPDC5, preventing it from inhibiting mTORC1 as it does normally, which in turn leads to pathogenic inflammation and cell growth in the liver [ 22 , 29 ]. Future research should explore how the rs1012068 and rs5998152 polymorphisms affect DEPDC5 expression and activity.…”
Section: Discussionmentioning
confidence: 99%
“…This was ascertained by another study which reported 40% increased risk of severe fibrosis with DEPDC5 rs1012068 T/G gene polymorphism. 15 Hepatic fibrogenesis is a pathophysiological outcome of chronic liver injury characterized by excessive accumulation of extracellular matrix proteins. 16 An in vitro study on immortalized hepatic stellate cells (HSCs) with high DEPDC5 expression was performed.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, our findings can find its explanation based on researchers who reported that DEPDC5 gene pathogenic G variant is an inactivating variant leading to down-regulation of the encoded DEPDC5 protein. 15 Furthermore, down-regulation of the DEPDC5 protein caused by DEPDC5 gene polymorphism leads to decreasing its blocking effect on mTOR signaling pathway. 8,15 The consequent increased activity of the mTOR pathway promotes fibrosis through transforming growth factor-β (TGF-β) independent mechanism, 17 which is considered as another explanation of the molecular basis of genetic association of DEPDC5 variants with fibrosis progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding HCC as a consequence of HCV infection, host genetics also play an essential role. For example, the single-nucleotide polymorphisms (SNPs) rs2596542, rs1012068, rs17047200, and rs2856723 of the genes MICA , DEPDC5 , TLL1 , and HLA-DBQ1 , respectively, were found to be significantly associated with HCC development in patients with HCV [ 21 ].…”
Section: Introductionmentioning
confidence: 99%